History and beyond : trends and trajectories - Mukherjee, Jenia; Palit, Chittabrata (New Delhi Kunal Books, 2014)
Papers presented at a seminar held at Jadavpur University in July 2012.
section 1. Gender and cultural studies -- section 2. Environmental history and literature -- section 3. Military and radical history -- section 4. Tribal history and labour studies -- section 5. Various aspects of contemporary history.
Includes bibliographical references and index.
Keywords: Human ecology -- India -- History -- Congresses; Human ecology -- India -- West Bengal . -- History -- Congresses; Women -- India -- Social conditions